2020
DOI: 10.1186/s13046-020-01690-z
|View full text |Cite
|
Sign up to set email alerts
|

TM4SF1 promotes EMT and cancer stemness via the Wnt/β-catenin/SOX2 pathway in colorectal cancer

Abstract: Background Transmembrane 4 L six family member 1 (TM4SF1) is upregulated in several epithelial cancers and is closely associated with poor prognosis. However, the role of TM4SF1 and its potential mechanism in colorectal cancer (CRC) remain elusive. Methods We investigated the expression of TM4SF1 in the Oncomine, the Cancer Genome Atlas (TCGA) and Gene Expression Omnibus (GEO) databases and confirmed the results by immunohistochemistry (IHC), qPCR and Western blotting (WB) of CRC tissues. The effect of TM4SF… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

4
119
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 194 publications
(123 citation statements)
references
References 47 publications
4
119
0
Order By: Relevance
“…8). TM4SF1, a member of the tetraspanin family, has been identified as a tumour-specific antigen, promoting proliferation, invasion, epithelial-mesenchymal transition (EMT) and chemoresistance [39][40][41] . Expression of TM4SF1 marks stem cell in mesenchymal tissue 42 and lung 43 .…”
Section: Discussionmentioning
confidence: 99%
“…8). TM4SF1, a member of the tetraspanin family, has been identified as a tumour-specific antigen, promoting proliferation, invasion, epithelial-mesenchymal transition (EMT) and chemoresistance [39][40][41] . Expression of TM4SF1 marks stem cell in mesenchymal tissue 42 and lung 43 .…”
Section: Discussionmentioning
confidence: 99%
“…24 The inhibition of Nanog and SOX2 can reduce the proliferation of colorectal cancer stem cells. 25,26 Here, we identified Nanog and SOX2 were enriched in adenomas, suggesting that they may contribute to the development and evolution of adenomas.…”
Section: Discussionmentioning
confidence: 74%
“…As a pivotal mediator in tumor development, transforming growth factor-β1 (TGF-β1) is embroiled in mediating carcinogenesis and metastasis through activating its downstream small mother against decapentaplegic (Smad) signaling [ 52 , 53 ]. Recent works have revealed that Wnt/β-catenin pathway inhibition inverts TGF-β-mediated EMT of tumor cells [ 54 , 55 ]. Growth differentiation factor 8 (GDF8) facilitates cell invasiveness in human trophoblasts by uplifting FSTL3 expression through the ALK5-SMAD2/3 signaling pathway [ 56 ].…”
Section: Discussionmentioning
confidence: 99%